Impact of carbamylation on three different methods, HPLC, capillary electrophoresis and TINIA of measuring HbA1c levels in patients with kidney disease. Issue 1 (April 2015) - Dolscheid-Pommerich, Ramona C.; Kirchner, Sonja; Weigel, Carola; Eichhorn, Lars; Conrad, Rupert; Stoffel-Wagner, Birgit; Zur, Berndt
Highlights Comparison of three different measurement methods for HbA1c determination. Based on nephrology samples, HbA1c measurements could result in different diagnoses. Carbamylated hemoglobin was assessed based on determination of BUN levels in serum. Weak influence of carbamylation in all methods.